Academic Star Wars: Excellence Initiatives in Asia and Europe - Salmi, Jamil; Altbach, Philip; Yudkevich, Maria (International Higher Education, 2024)
Academic excellence initiatives have been introduced around the world in an effort to quickly improve research universities, research culture, and the rankings of top universities. Academic Star Wars, a recently published book, examines nine case studies of such initiatives in Europe and Asia. The AEIs impact on academic culture, productivity, and in some cases governance has been significant.